The social impact of universities: assessing the effects of the three university missions on social engagement - Carl, Johannes; Menter, Matthias (Studies in Higher Education, 2021)
Whereas the economic impact of universities is undisputed, the social impact of universities remains vague. The purpose of this paper is to examine whether and how universities influence firms’ social engagement. Based on survey data of more than 7,000 German firms, our results reveal that universities positively affect firms’ social engagement mainly through teaching activities. Hence, our findings give impetus to a reinforcement of the university mission ‘teaching’ as a central lever for social change and increased social awareness as well as to a reorientation of the third university mission toward social needs. This paper thereby contributes to our understanding of the changing missions and values of universities and adds to the literature by exploring the underlying mechanisms of the social impact of universities. We conclude the paper with fruitful future avenues of research.
Number: 5
Keywords: Europe; Réservé UdeM; Rôle des universités